A partial fuel energy answer for America : electric bikes - Ayres, Robert U. (FTPress Delivers elements., 2010)
This Element is an excerpt from Crossing the Energy Divide (ISBN: 9780137015443) by Robert U. Ayres and Edward H. Ayres. Available in print and digital formats. How electric bikes may help reshape urban transportation--slashing fuel use and carbon emissions, and improving convenience, too. Battery-equipped electric-bikes have the potential to change the commuter game radically. Even if limited to 15-20 mph, they'll be able to use the bike paths or reserved lanes many cities are building into their plans. If just 20-30% of short urban trips shift to "e-bikes," fuel use will drop enough to help bridge us to a cleaner, more secure energy future....